Organization of Eastern Caribbean States : Policy Note on Project Fiduciary Management - World Bank (Washington, DC, 2014)
The Organization of Eastern Caribbean States (OECS) face special development challenges, including limited institutional capacity, high per capita costs of basic social and infrastructure services, and vulnerability to natural disasters and other external shocks. This note identifies specific issues related to financial management and procurement. This note focused on the implications of differing donor practices for financing capital projects in a generally weak institutional and implementation environment for capital projects. The quality of implementation is also affected by a lack of adequate project management skills. The objective of this Policy Note is to increase the efficiency of capital investment project implementation in the OECS countries by (i) contributing to a more efficient use of limited institutional and human resource capacity, (ii) lowering transaction costs, and (iii) optimizing the use of public funds, while (iv) maintaining a robust control framework. The OECS economies are highly dependent on donor assistance for funding investment projects. This note identifies opportunities for sequential mainstreaming of fiduciary functions (financial management and procurement) and for a gradual approach to using mechanisms. The OECS countries' current efforts to rationalize institutional arrangements for capital projects by consolidating implementing entities or further mainstreaming implementation within existing structures in line ministries are consistent with the recommendations of the Country Program Quality Enhancement Review conducted by the World Bank in 2004.